Analisis Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Pada Fa. Banang Jaya - Tiberiusman Gulo; Lili Suryati; Ripka Seri Idahnaita Ginting (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The purpose of this study was to determine the effect of product quality, price, promotion on purchasing decisions at Fa Banang Jaya (study on Ikad Ceramics). The method used in this study is a quantitative method. In the research conducted, the authors use two types of data to help solve the problem, namely primary data and secondary data. The population in this study are consumers who make purchases at the Fa Banang Jaya were 113 consumers for two months since February to March 2022. Due to the total population of 113 consumers, the number will be reduced by usng the slovin sample technique. The number of samples used in this study were 54 respondents.The data analysis techniques used were validity and reliability tests, classical assumption test, multicollinearity test, heteroscedasticity test, partial test (t test), simultaneous test (F). ), Multiple linear regression analysis and coefficient of determination (R2). The results showed that partially the product quality has a positive and significant effect on purchasing decisions at Fa Banang Jaya. Price has a negative and significant effect on purchasing decisions at Fa Banang Jaya. Promotion has a positive and significant effect on purchasing decisions at Fa Banang Jaya. The test results showed that simultaneously product quality, price and promotion have a significant effect on purchasing decisions at Fa Banang Jaya.The coefficient of determnation test shows that the independent variables can explain the purchasing decisions at 51,4 percent